Theses and Dissertations Completed in Family and Consumer Sciences: 2019. (11th November 2020) - Wilmarth, Melissa J.; Milstead, S. Morgan
Abstract : The annual survey of graduate programs in family and consumer sciences at U.S. universities and colleges was conducted in June 2020. The project's goal was to assemble a listing of theses and dissertations completed in 2019 from all areas of family and consumer sciences. Representatives at institutions with identified family and consumer sciences programs were e‐mailed requests for information regarding completed theses and dissertations. Twenty‐five colleges and universities responded. The final total was a total of 214 theses and 195 dissertations were completed within participating graduate programs in 2019. This report includes the submitted information on theses and dissertations by subject category.